Outcomes in diabetic patients undergoing primary percutaneous coronary intervention for acute anterior myocardial infarction: Results from the INFUSE‐AMI study. Issue 5 (23rd October 2013) - Sanidas, Elias A.; Brener, Sorin J.; Maehara, Akiko; Généreux, Philippe; Witzenbichler, Bernhard; El‐Omar, Magdi; Fahy, Martin; Mehran, Roxana; Gibson, C. Michael; Stone, Gregg W.
<x xml:space="preserve">Abstract</x> Objectives To evaluate the clinical, angiographic, and cardiac magnetic resonance imaging (cMRI) results in patients with and without diabetes mellitus (DM) undergoing primary percutaneous coronary intervention (PCI) for ST‐elevation myocardial infarction (STEMI). Background DM has been associated with increased mortality in patients with STEMI, yet the mechanisms underpinning this association have not been completely elucidated. Methods Overall, 451 patients (51 diabetics) from the INFUSE‐AMI trial were studied. They presented with an anterior STEMI due to an occluded left anterior descending artery (LAD) and underwent bivalirudin‐supported primary PCI with or without intralesion abciximab and with or without thrombus aspiration. Angiographic baseline and post‐procedure parameters, cMRI at 30 days, and clinical follow‐up at 30 days and at 1 year were compared between diabetic and nondiabetic patients. Results Patients with DM had significantly more comorbidities and more extensive LAD disease than nondiabetics. Primary PCI was equally effective in restoring coronary flow in both groups and the infarct size at 30 days was similar (14.3% [7.1, 24.5] vs. 17.3% [8.1, 23.6], respectively, P = 0.55). Diabetic patients had more major cardiovascular and cerebrovascular events at 1 year (16.5% vs. 8.0%, P = 0.04). Stent thrombosis within 30 days after primary PCI was higher in diabetic than in nondiabetic subjects (4.3% vs. 0.8%, P = 0.03). Conclusions Patients with DM presenting with STEMI had a higher baseline risk profile than those without DM. Although reperfusion success and infarct size were similar, diabetic patients experienced more death, reinfarction, stent thrombosis, and revascularization than nondiabetics. © 2013 Wiley Periodicals, Inc.